Treatment (biotherapy excluded) of psoriatic arthritis: an appraisal of methodological quality of international guidelines. Issue Volume 28:Issue S5 (2014)Supplement (August 2014) - Sevrain, M.; Villani, A.P.; Rouzaud, M.; Barnetche, T.; Paul, C.; Richard, M.‐A.; Beylot‐Barry, M.; Jullien, D.; Aractingi, S.; Aubin, F.; Joly, P.; Le Maitre, M.; et al.
Abstract: Background: Some international guidelines have been published to provide the best care for patients with psoriatic arthritis (PsA) but little is known about their quality. Objective: The primary aim of this study was to examine the quality of guidelines that concern treatment (biotherapy exluded) of PsA. The secondary aim was to review studies published since the publication of the most recent guideline. Methods: A systematic literature search was carried out from 2007 to February 2013, in the Embase, Medline and Cochrane Library databases, in English and French using a combination of keywords including 'Arthritis, Psoriatic/therapy' NOT 'Biological Therapy' OR 'Antibodies, Monoclonal' OR 'Recombinant Fusion Proteins' OR 'tumour necrosis factor‐alpha'. The AGREE instrument (Appraisal of Guidelines Research and Evaluation) was used by four reviewers to evaluate the quality of selected guidelines according to the proposed methodology. Results: Of the 518 identified references, six guidelines and two studies were selected. There was considerable variation in the quality of clinical guidelines across the AGREE domains. The least well‐addressed domains were 'applicability', 'stakeholder involvement', 'scope and purpose' and 'quality of development', whereas 'editorial independence' and 'clarity and presentation' were less problematic. Conclusion: Although guidelines development was of good quality, many of the studies that they included are of poorer quality. This work indicates that the current guidelines can be improved, particularly the stakeholder domain and the applicability domain. The prospective use of the AGREE instrument should improve the guideline quality. More controlled trials should be required but are unlikely to be conducted, given the lack of interest in studying old drugs.